Innovative IOP-Independent Neuroprotection and Neuroregeneration Strategies in the Pipeline for Glaucoma. (10th April 2020) - Tsai, James C.
Abstract : While sustained reduction of intraocular pressure (IOP) has been shown to halt and/or delay the progressive death of retinal ganglion cells (RGCs) in glaucoma, there exists great interest in the development and validation of IOP-independent therapeutic strategies for neuroprotection and/or neuroregeneration. Multiple etiologies for RGC death have been implicated in glaucoma including defective axonal transport, ischemia, excitotoxicity, reactive oxygen species, trophic factor withdrawal, and loss of RGC electrical activity. However, IOP lowering with medical, laser, and surgical therapies is itself neuroprotective, and investigators are seeking to identify agents that are able to confer neuroprotection independent of IOP reduction, as well as providing for regeneration of nonviable RGCs and their axons to restore and/or maintain functional vision. These innovative strategies in the pipeline include investigation of neurotrophic factors, gene therapy, immune system modulation, and novel neuroregeneration pathways. Alongside this new knowledge, enhanced opportunities for discovery of vision preservation and/or restoration therapies must be weighed against the potential disadvantages of perturbing the complex central nervous system environment.